Evidence of two mitochondrial lineages and genetic variability in forensically important Lucilia eximia (Diptera: Calliphoridae) in Colombia (2023)
ABSTRACT: Lucilia eximia (Wiedemann, 1819) (Diptera: Calliphoridae) is a blowfly with medical and forensic importance that shows genetic and color variation, however, these variations have not justified the description of new species. But in forensic entomology an accurate identification of species and subpopulations is crucial. We explored the genetic variation of L. eximia from eight localities, in five natural regions in Colombia using two mitochondrial fragments, including the standard locus for insect identification COI and the Cytb-tRNA-Ser-ND1 region. We found significant differentiation at COI and Cytb-tRNA-Ser-ND1 level, characterizing two lineages and revealing a deep and significant genetic split. High values of FST and genetic distances supported the two lineages. The origin of the divergence of L. eximia remains to discover. Examining whether the lineages have diverse ecological and biological behaviors could be a significant impact on the use of L. eximia in forensic and medical science. Our results could have relevant implications for the use of post-mortem interval estimation based on insect evidence, as well as our sequences improve the database used in DNA-based methods for identifying forensically important flies.